2016
DOI: 10.1021/acsami.6b00706
|View full text |Cite
|
Sign up to set email alerts
|

Water-Stable Anionic Metal–Organic Framework for Highly Selective Separation of Methane from Natural Gas and Pyrolysis Gas

Abstract: A 3D water-stable anionic metal-organic framework [Zn4(hpdia)2]·[NH2(CH3)2]·3DMF·4H2O (FJI-C4) was constructed based on an elaborate phosphorus-containing ligand 5,5'-(hydroxyphosphoryl)diisophthalic acid (H5hpdia). FJI-C4 with narrow one-dimensional (1D) pore channels exhibits high selectivity of C3H8/CH4 and C2H2/CH4. It is the first time for the MOF which contains phosphorus for selective separation of methane from natural gas and pyrolysis gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 40 publications
2
94
0
Order By: Relevance
“…The C 3 light hydrocarbons with higher adsorption enthalpy [Q st (C 3 H 6 ) > Q st (C 3 H 8 ) > Q st (C 2 H 2 ) > Q st (C 2 H 6 ) > Q st (C 2 H 4 ) > Q st (CH 4 )] may provide as tronger affinity for the skeleton, whichr esults in preferentiala dsorptiono ft hese gases on the skeleton of UPC-33.T hus, it may have ah igh selectivity for C 3 light hydrocarbonsr elative to CH 4 .T herefore the potential for separation of CH 4 from C 3 light hydrocarbons is appraisedb yi deal solution adsorbed theory (IAST) for binarye quimolar components (Figure 3d). At 1bar and 273 K, the selectivities of C 3 H 8 and C 3 H 6 with respectt oC H 4 are 151.50 and 228.34, which are higher than C 2 H 2 ,C 2 H 4 ,a nd C 2 H 6 to CH 4 of 11.36, 5.32, and 6.64, respectively.I ts hould be notedt hat thesev alues are lower than FJI-C4 (293.4 for C 3 H 8 /CH 4 ), [29] but greatly higher than UPC-21 (75 for C 3 H 6 /CH 4, 67 for C 3 H 8 /CH 4 ), [9] or FJI-C1 (78.7 for C 3 H 8 /CH 4 ). [31] The results indicatethat UPC-33 is aprospectivea bsorbent for effectively selective adsorptive separation of CH 4 from C 3 hydrocarbons at 273 K. The high adsorption selectivity of C 3 /CH 4 can be attributed to the narrow pore size distribution of UPC-33 to match the kinetic diameter of C 3 light hydrocarbon, resulting in its high C 3 /CH 4 sievinge ffects.…”
Section: Gas Adsorption and Separationmentioning
confidence: 81%
See 1 more Smart Citation
“…The C 3 light hydrocarbons with higher adsorption enthalpy [Q st (C 3 H 6 ) > Q st (C 3 H 8 ) > Q st (C 2 H 2 ) > Q st (C 2 H 6 ) > Q st (C 2 H 4 ) > Q st (CH 4 )] may provide as tronger affinity for the skeleton, whichr esults in preferentiala dsorptiono ft hese gases on the skeleton of UPC-33.T hus, it may have ah igh selectivity for C 3 light hydrocarbonsr elative to CH 4 .T herefore the potential for separation of CH 4 from C 3 light hydrocarbons is appraisedb yi deal solution adsorbed theory (IAST) for binarye quimolar components (Figure 3d). At 1bar and 273 K, the selectivities of C 3 H 8 and C 3 H 6 with respectt oC H 4 are 151.50 and 228.34, which are higher than C 2 H 2 ,C 2 H 4 ,a nd C 2 H 6 to CH 4 of 11.36, 5.32, and 6.64, respectively.I ts hould be notedt hat thesev alues are lower than FJI-C4 (293.4 for C 3 H 8 /CH 4 ), [29] but greatly higher than UPC-21 (75 for C 3 H 6 /CH 4, 67 for C 3 H 8 /CH 4 ), [9] or FJI-C1 (78.7 for C 3 H 8 /CH 4 ). [31] The results indicatethat UPC-33 is aprospectivea bsorbent for effectively selective adsorptive separation of CH 4 from C 3 hydrocarbons at 273 K. The high adsorption selectivity of C 3 /CH 4 can be attributed to the narrow pore size distribution of UPC-33 to match the kinetic diameter of C 3 light hydrocarbon, resulting in its high C 3 /CH 4 sievinge ffects.…”
Section: Gas Adsorption and Separationmentioning
confidence: 81%
“…UPC-33 exhibits an adsorption amount of 93.6 and 94.3 cm 3 g À1 for C 3 H 8 and C 3 H 6 at 298 Ka nd 1bar,w hich are slightly lower than that of UPC-21 (103.0 and 110.1 cm 3 g À1 ), [9] and higher than FJI-C4 (74.7 cm 3 g À1 for C 3 H 8 ). [29] Considering its practical application, we also tested the reproducibility of UPC-33 for C 3 H 8 and C 3 H 6 storage. About 100 mg of the desensitized sample was loaded onto the ASAP2020-M analyzer,a nd four cycles of C 3 H 8 and C 3 H 6 adsorption at 298 Kw erer ecorded withoutt he reactivation process between each cycle.…”
Section: Gas Adsorption and Separationmentioning
confidence: 99%
“…In recent years, metal–organic frameworks (MOFs) have been applied widely in numerous fields, which include molecular separation and heterogeneous catalysis, because of their high surface area/porosity, tunable pore apertures/window size, and many other outstanding properties . The use of highly porous MOFs as hosts to confine effective POMs (POM@MOF) is a promising strategy to prepare catalysts for ODS with a high activity and good recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of binary gas mixtures can be directly predicted from pure component adsorption data using ideal adsorbed solution theory (IAST) proposed by Myers and Prausnitz [27]. Many studies have confirmed the effectiveness of IAST to predict the adsorption of mixture gases on a variety of porous materials [28][29][30].…”
Section: Ideal Adsorbed Solutionmentioning
confidence: 99%